Between Technological Determinism and Public Interest: Limits and Possibilities of Internet Regulation (Law, State and Telecommunications Review, 2019)
Purpose ”“ The paper deals with the regulation of the internet, presenting the controversies between those in favor of the exceptionalism and those in favor of more control and rights protection.  Adopting a wide and decentralized view of regulation, and a comprehension of the technology as embedded in social relations, we sustain the possibility of internet regulation, which must be centered on Tony Prosser’s regulation theory. Methodology/approach/design ”“ The paper starts with the search of an operational concept of internet regulation and governance, analyzing the consequences of the adoption of a wide and decentralized conception of regulation. Then, we present the libertarians and paternalists theses of internet regulation, which are in the root of the internet exceptionalism/regulability debate. Then, with support in Lawrence Lessig and Andrew Murray internet regulation theories, we analyze the technological determinist approach. Findings ”“ Based on the previous considerations we set minimum parameters so that the internet regulation is understood from a perspective of protection of the public interest.